Multi-period lot-sizing with supplier selection: Structural results, complexity and algorithms - Lin, Meichun; Huh, Woonghee Tim; Wan, Guohua (Operations research letters, 2021)
We consider a multi-period lot-sizing problem with multiple products and multiple suppliers. Demand is deterministic and time-varying. The objective is to determine order quantities to minimize the total cost over a finite planning horizon. This problem is strongly NP-hard. For a special case, we extend the classical zero-inventory-ordering principle and solve it by dynamic programming. Based on this new extension, we also develop a heuristic algorithm for the general problem and computationally show that it works well.